Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1172/jci115130
|View full text |Cite
|
Sign up to set email alerts
|

A plasma protease which is expressed during supramaximal stimulation causes in vitro subcellular redistribution of lysosomal enzymes in rat exocrine pancreas.

Abstract: The complex events by which digestive enzyme zymogens and lysosomal hydrolases are segregated from each other and differentially transported to their respective membrane-bound intracellular organelles in Invest. 1991Invest. .87:1280Invest. -1285

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…They also found in in vitro experiments that incubation of pancreas fragments with a supramaximal concentration of cerulein did not result in the redistribution of lysosomal enzymes; however, the redistribution of lysosomal hydrolases was observed when fragments were incubated with cerulein along with rat plasma obtained from cerulein-induced pancreatitis [33]. Our observation that neutrophil depletion ameliorated pancreatic injury during the early stages in ceruleininduced pancreatitis led us to conclude that neutrophils might worsen the pancreatic injury.…”
Section: Discussionsupporting
confidence: 63%
“…They also found in in vitro experiments that incubation of pancreas fragments with a supramaximal concentration of cerulein did not result in the redistribution of lysosomal enzymes; however, the redistribution of lysosomal hydrolases was observed when fragments were incubated with cerulein along with rat plasma obtained from cerulein-induced pancreatitis [33]. Our observation that neutrophil depletion ameliorated pancreatic injury during the early stages in ceruleininduced pancreatitis led us to conclude that neutrophils might worsen the pancreatic injury.…”
Section: Discussionsupporting
confidence: 63%
“…However, regardless of whether only intracellular targeting or also the mechanism of endocytosis is altered, the consequence is an intracellular colocalization of lysosomal and digestive hydrolases. Such a colocalization has previously been observed in two unrelated models of pancreatitis, and we proposed it to be a critical event for the intracellular activation of proteases in pancreatitis (30,31 ). In those studies, however, fusion of lysosomes with zymogen granules was thought to be the source of colocalization, whereas in the present investigation, uptake from the lumen appears as a novel alternative.…”
Section: Discussionsupporting
confidence: 48%
“…We have previously shown that the intracellular transport and sorting of proteins are markedly altered in early acute experimental pancreatitis (31 ) and after P-BD obstruction (32). During transport of newly synthesized enzymes through the cell, a missorting from the lysosomal into the regulated secretory pathway was observed (28).…”
Section: Discussionmentioning
confidence: 99%
“…The lysosom al activation hypothesis is based on two observations: (1) Cathepsin B can rapidly catalyze the conversion of trypsinogen to trypsin in vitro [57] and does so over a wide range of pH which is compatible with in vivo condi tions [58]. (2) In all experimental animal models of pan creatitis cathepsin B shifts into a zymogen granuleenriched fraction obtained by subcellular fractionation experiments [59,60], Accordingly it was proposed that early in pancreatitis cathepsin B and trypsinogen become newly colocalized in an intracellular compartment that has a greater density than lysosomes and probably corre sponds to the large cytoplasmic vacuoles observed during pancreatitis [61]. Although these experimental observa tions are undebated, their relevance as to the premature activation of trypsinogen has been questioned.…”
Section: Hypotheses For Enzyme Activationmentioning
confidence: 99%